EFEKTIVITAS BIMBINGAN KLASIKAL MENGGUNKAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERNALAR KRITIS BELAJAR SISWA KELAS VIII SMP 37 MEDAN - Inggrit Sabrina; M Fauzi Hasibuan (ADIBA : JOURNAL OF EDUCATION, 2024)
This study aims to determine the effectiveness of classical guidance using the Problem Based Learning approach in improving critical reasoning skills of class VIII students of SMP 37 Medan. The research method used is quantitative experiment with pretest-posttest control group design. The subjects of the study consisted of 60 students divided into an experimental group (30 students) and a control group (30 students). The experimental group was given treatment in the form of classical guidance with the Problem Based Learning approach, while the control group was only given ordinary classical guidance. Data collection used a Likert scale questionnaire. The results showed a significant increase in critical reasoning skills in the experimental group with an average pretest score of 85.13 (moderate category) to 124.3 (very high category) on the posttest. While in the control group there was an increase from an average of 85.06 (moderate) to 120.53 (high). The Wilcoxon and Kolmogorov-Smirnov tests showed a significant difference between the experimental and control groups (p <0.05). It is concluded that classical guidance with the Problem Based Learning approach is effective in improving students' critical reasoning ability in learning.